Eldecalcitol prevents muscle loss by suppressing PI3K/AKT/FOXOs pathway in orchiectomized mice - Zhang, Haichao; Ke, Zheng; Dong, Shuangshuang; Du, Yanping; Tang, Wenjing; Chen, Minmin; Yu, Weijia; Cheng, Qun (Frontiers in Pharmacology, 2022)
Elderly male patients are susceptible to developing osteoporosis and sarcopenia, especially those with fragility fractures, hypogonadism, and prostate cancer with androgen deprivation therapy. However, at present, very few treatments are available for men with sarcopenia. Previous preclinical studies in ovariectomized rats have shown the promising effects of eldecalcitol in ameliorating bone strength and muscle atrophy. We thus investigated the effects of eldecalcitol on androgen-deficient male mice. Six-week-old male mice underwent orchiectomy (ORX) or sham surgery. Mice were randomly divided into 4 groups (n = 12/per group), including (i) sham mice, (ii) ORX group, (iii) ORX eldecalcitol 30 ng/kg, and (iv) ORX eldecalcitol 50 ng/kg. Eldecalcitol increased bone mass and strength of femur in ORX mice. Eldecalcitol 30 ng/kg dose completely rescued ORX-induced muscle weakness. The RT-qPCR showed that eldecalcitol enhanced the mRNA levels of type I and IIa fibers. The expression levels of MuRF1 and Atrogin-1 of gastrocnemius in the eldecalcitol groups were much lower than that of the ORX group. It is assumed that eldecalcitol potentially acts via PI3K/AKT/FOXOs signaling pathway. These findings provide evidence for evaluating eldecalcitol as an investigational treatment for male patients with sarcopenia and osteoporosis.